Anastomotic leak: an early complication with potentially long-term consequences - Schlottmann, Francisco; Molena, Daniela (Journal of Thoracic Disease, 2016)
Significant improvements in surgical techniques and postoperative care have led to a reduction in morbidity and mortality associated with esophagectomy (1). Nevertheless, anastomotic leak remains the most feared complication and represents the Achilles’ heal of esophageal resection. The overall risk of developing an anastomotic leak is about 10%, with significant higher incidence for cervical anastomosis compared to intrathoracic (2).